Anti-inflammatory Microglia/Macrophages As a Potential Therapeutic Target in Brain Metastasis - Andreou, Kleopatra E.; Soto, Manuel Sarmiento; Allen, Danny; Economopoulos, Vasiliki; de Bernardi, Axel; Larkin, James R.; Sibson, Nicola R. (Frontiers in Oncology, 2017)
Brain metastasis is a common complication of cancer patients and is associated with poor survival. Histological data from patients with brain metastases suggest that microglia are the major immune population activated around the metastatic foci. Microglia and macrophages have the ability to polarise to different phenotypes and to exert both tumorigenic and cytotoxic effects. However, the role of microglia/macrophages during the early stages of metastatic growth in the brain has not yet been determined. The aim of this study was to profile microglial/macrophage activation in a mouse model of breast cancer brain metastasis during the early stages of tumour growth, and to assess the role of the anti-inflammatory microglial population, specifically, during this phase. Following intracerebral injection of 5x103 4T1-GFP mammary carcinoma cells into female BALB/c mice robust microglial/macrophage activation around the 4T1 metastatic foci was evident throughout the time-course studied (28 days) and correlated positively with tumour volume (r2=0.67). Populations of classically (pro-inflammatory) and alternatively (anti-inflammatory) activated microglia/macrophages were identified immunohistochemically by expression of either iNOS/COX2 or MRC1/Arg1, respectively. Temporally, levels of both pro- and anti-inflammatory cells were broadly stable across the time-course. Subsequently, selective depletion of the anti-inflammatory microglia/macrophage population by intracerebral injection of mannosylated clodronate liposomes significantly reduced metastatic tumour burden (p<0.01). Moreover, increased levels of apoptosis were associated with tumours in clodronate liposome treated animals compared to controls (p<0.05). These findings suggest that microglia/macrophages are important effectors of the inflammatory response in the early stages of brain metastasis, and that targeting the anti-inflammatory microglial/macrophage population may offer an effective new therapeutic avenue for patients with brain metastases.